Transdisciplinary Connections : Afro-Latin America meets Bayreuth - Gruber, Valerie (NAB : News from the Institute of African Studies at the University of Bayreuth, 2021)
After two years of virtual collaboration on questions of the African diasporas, three Latin American research partners of the Cluster project Moral Geographies of Re-Existence visited Bayreuth in 2021: Rigoberto Banguero Velasco, Laís Machado, and Diego Araúja. Their guest stays set the project’s transdisciplinary knowledge production afloat.